Location, Location, Location Revisited : Evidence from Antananarivo, Madagascar - Iimi, Atsushi (World Bank, Washington, DC, 2019)
Understanding how land prices are determined is of particular importance for policy makers; however, there is little evidence in African countries, which are currently experiencing rapid urbanization. The paper examines the relationship between land prices and locational characteristics using data from Antananarivo, the capital of Madagascar. It is found that the land value gradients are relatively steep, indicating that the land and housing prices tend to overshoot in the middle of the city, pushing the poor away from the city to suburban areas. It is also found that access to transport infrastructure and services, such as minibuses, is an important determinant of land value. Not only transport connectivity, but also other factors, such as proximity to amenities and administrative centers, are found to be important. Better land management and urban transport policies are called for to promote these aspects in the city.